Effectiveness of private military companiesin international political - Samar Mahdi jabbar (The college of law and political science journal, 2025)
The increasing development of private military companies, represented by efficiency, experience, readiness, speed and accuracy in accomplishing the tasks and objectives assigned to them, has made the increasing dependence on them by countries a tangible and realistic matter in the current era, especially with the change in international politics that is witnessing in addition to the pressures of globalization and the major powers that stand behind these companies they are sponsored and protected by international laws, in light of the great influence of major powers in international politics, which has led to an increase in the number of private military companies, their development, and their influence in international politics to the point that they have begun to compete with national powers and local governments within the same countries because of their experience and specialized technology in areas that may not be Available in national governments of countries.